Η Αυτοεκτίμηση και Κοινωνική Αποδοχή Μαθητών Τμημάτων Ένταξης - Σουσαμίδου, Αικατερίνη; Αναγνωστοπούλου, Μαρία (Επιστήμες Αγωγής, 2017)
Αttending integration class is a factor that makes pupils facing learning and behavioral problems differ from their peers who attend courses only in the normal class. The main purpose of this study was to investigate self-esteem and social acceptance by peers of the pupils of the Integration class. The survey involved 110 students (55 of integration class and 55 of normal class) of the last three grades of primary school. As a research tool the questionnaire “How I see myself II” for the last three grades of elementary school was used counting only scales “Relations with peers” and “Self-esteem”. The results were analyzed with the statistical package SPSS, defining as independent variables age and sex of the participating pupils. It was found that self-esteem and social acceptance of pupils of the integration class did not differ from their peers who attend courses only in the normal class.